Morphodynamics of Recherchefjorden accumulative coasts since the end of the Little Ice Age - Frydrych, Kamila; Zagórski, Piotr (Quaestiones Geographicae, 2024)
The shores of Recherchefjorden in western Spitsbergen have undergone significant changes during the 20th and early 21st centuries, resulting from the end of the Little Ice Age (LIA) and climate warming. In areas exposed by retreating glaciers, paraglacial processes have had an impact, leading to the development of forms such as spits, lagoons and beaches. The main factors that determine the direction of landform development include wave patterns, the role of longshore currents in material transport, and the state of the fjord’s sea/coast ice. Archival materials such as aerial and satellite photos and geomorphological mapping were used to analyse changes in the length of accumula- tion forms in Recherchefjorden. Nine accumulation areas were identified along the fjord’s shores. Longshore currents’ primary directions were determined by the arrangement of accumulation forms, flowing southward along the western coast from the Chamberlinelva estuary to Rubypynten, and westward on the eastern outwash plain of Recherchebreen. Material transport along the fjord’s eastern coast is mainly towards the south. Following the LIA, the accumulation rate increased, with the highest values recorded in the second and early third decades of the 21st century. Longshore currents shape accumulation forms such as spits and beaches, but they appear intermittently depending on favourable wave and tidal conditions, transforming coasts and accumulating material through longshore drift. These conditions occur periodically and independently of water circulation or tidal currents, allowing accumulation forms to develop in leaps under intensive material supply, ensuring their stability.